Wearable Lumbar-Motion Monitoring Device with Stretchable Strain Sensors. (8th October 2018) - Nakamoto, Hiroyuki; Yamaji, Tokiya; Yamamoto, Akio; Ootaka, Hideo; Bessho, Yusuke; Kobayashi, Futoshi; Ono, Rei
Abstract : Low-back pain is a common affliction. Epidemiological analyses have reported that periodic cycles of lumbar flexion and rotation are major risk factors for low-back pain. To prevent low-back pain, a lumbar-motion monitoring device could help diagnosticians assess patients' risk for low-back pain. This study proposes such a device that uses lightweight stretchable strain sensors. Six of these strain sensors form a parallel-sensor mechanism that measures rotation angles of lumbar motion in three axes. The parallel-sensor mechanism calculates rotation angles from the lengths of the strain sensors iteratively. Experimental results reveal that the prototype device is effective for lumbar-motion measurement and significantly improves in terms of wearability over comparable devices.